Innovation ecosystems and start-ups in the Mediterranean as a means of recovering from the COVID-19 crisis - Sidło, Katarzyna (European Committee of the Regions, 2021)
The ability to innovate and to make use of new technologies and techniques is indispensable for economic diversification and sustainable development. It is not easy to define innovation, as it is a much broader concept than just capacity to devise new high-tech products and solutions. Indeed,
10.2863/518444
Keywords: Graue Literatur; Innovationssystem; Unternehmensgründung; Gründungsfinanzierung; Coronavirus; Epidemie; Technische Zusammenarbeit; Mittelmeerraum; EU-Staaten; coronavirus disease; innovation; start-up; cooperation policy; development policy; information technology; new technology; regional and local authorities; sustainable development; added value; crisis management; Mediterranean region (EU); report